Education and Training of Child in the Speech of Khushal Khan - Himat, Ghulam Sakhi (Integrated Journal for Research in Arts and Humanities, 2024)
Training and education of a child is a huge responsibility of parents and should be taken into account. The holy religion of Islam also emphasizes on the education and training of children and is considered as the right of the children on parents, because children are the backbone of the society. Khushal Khan has focused on the education and training of the child in a wide range. He has written and recommended a lot regarding to the education and training of children. He has expressed his views both in prose and poems about the training and education of children. He has discussed the rights of the children in some parts of his work either. Education and training of children is the main idea of Khushal Khan;s article, Dastarnama.